Identification of an autophagy‐related prognostic signature in head and neck squamous cell carcinoma. (18th August 2021) - Jiang, Yue; Li, Yuanyuan; Ge, Han; Wu, Yaping; Zhang, Yuchao; Guo, Songsong; Zhang, Ping; Cheng, Jie; Wang, Yanling
Abstract: Background: Autophagy‐related genes (ARGs) have been significantly implicated in tumorigenesis and served as promising prognostic biomarkers for human cancer. Hence, this study was aimed to develop an ARGs‐based prognostic signature for Head and neck squamous cell carcinoma (HNSCC). Methods: Prognostic ARG candidates were identified by univariate and multivariate Cox regression analysis in the training dataset (TCGA‐HNSC) and incorporated into a 3‐ARGs ( EGFR, FADD, and PARK2 ) prognostic signature which was further verified in two independent validation cohorts (GSE41613 and GSE42743 ). Kaplan‐Meier plots, Cox regression analyses, and receiver operating characteristics curves (ROC) were employed to evaluate the prognostic prediction of 3‐ARGs signature. Differential expression of these 3 ARG between cancer and normal counterparts as well as their associations with autophagy markers were assessed in 60 pairs of freshly collected HNSCC and adjacent non‐tumor samples and datasets from Human Protein Atlas, respectively. Results: Patients with high‐risk score had significantly inferior overall survival. Multivariate regression analyses revealed that 3‐ARGs signature could be an independent prognostic factor after adjusting various clinicopathological parameters. ROC analyses revealed high predictive accuracy and sensitivity of the 3‐ARGs signature. Increased mRNA and protein expression of EGFR, FADD, and PARK2 were found in HNSCC samples, and their expression significantly correlated with the abundances of ATG5, Beclin1, and LC3 . Conclusion: Our results reveal that 3‐ARGs signature is a powerful prognostic biomarker for HNSCC, which could be integrated into the current prognostic regime to realize individualized outcome prediction. EGFR, FADD, and PARK2 likely contributed to autophagy during HNSCC tumorigenesis.